2021
DOI: 10.1063/5.0060706
|View full text |Cite
|
Sign up to set email alerts
|

High quality planar Cd1-xMnxTe room-temperature radiation detectors

Abstract: Cd1-xMnxTe is a promising material that has been introduced as a potential successor for the popular Cd1-xZnxTe material in the field of room-temperature gamma-ray detection. In this work, we demonstrate a planar array on a 5 mm thick Cd1-xMnxTe detector with spectroscopy performance similar to that of industrial Cd1-xZnxTe devices of the same thickness. The uniformity of Cd1-xMnxTe was theoretically predicted and experimentally demonstrated to be superior to that of Cd1-xZnxTe due to a better solubility of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Brovko et al. [ 7 ] showed that chemical polishing formed Te‐rich surfaces and resulted in high surface potentials. Zha et al.…”
Section: Introductionmentioning
confidence: 99%
“…Brovko et al. [ 7 ] showed that chemical polishing formed Te‐rich surfaces and resulted in high surface potentials. Zha et al.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Brovko et al. [ 9 ] confirmed that CMT crystals had better lateral and depth uniformity than CZT crystals. Secondly, they are direct bandgap crystals.…”
Section: Introductionmentioning
confidence: 99%